Organizing Committee: QAI 2025 (2025 IEEE International Conference on Quantum Artificial Intelligence (QAI), 2025)
Introduction In this prespecified analysis of a clinical trial to assess the effect of linkage case management on posthospital outcomes in people with HIV, we sought to evaluate the sustainability of the intervention effects from 12 to 24 months. Methods Participants in the Daraja trial were followed 12 months beyond the primary end point of 12 months to assess the sustainability of HIV outcomes 24 months after hospital discharge. Study outcomes were continuity in HIV care, persistent ART adherence, and sustained viral load suppression through 24 months, achieved at both 12-month and 24-month time points. Results Findings from 12 months after Daraja intervention completion indicate the sustainable effects of linkage case-management in people with HIV who had been hospitalized at the time the intervention was initiated. Intervention participants achieved higher rates of continuity in HIV care (78.6% vs 66.3%, P = 0.008), persistent ART adherence (74.1% vs 61.0%, P = 0.006), and persistent HIV viral load suppression (70.1% vs 57.6%, P = 0.01) compared with the standard of care sustained from through 24 months. The intervention effect on time to HIV clinic linkage and ART initiation also remained significant at 2 years with >10% of control participants remaining untreated after 2 years. Conclusions The Daraja intervention had a sustained effect on retention in HIV care, ART adherence, and viral load suppression among hospitalized people with HIV.